Developing a Strategic Approach to MOOCs. Issue 1 (28th December 2016) - Ferguson, Rebecca; Scanlon, Eileen; Harris, Lisa
During the last eight years, interest in massive open online courses (MOOCs) has grown fast and continuously worldwide. Universities that had never engaged with open or online learning have begun to run courses in these new environments. Millions of learners have joined these courses, many of them new to learning at this level. Amid all this learning and teaching activity, researchers have been busy investigating different aspects of this new phenomenon. In this contribution we look at one substantial body of work, publications on MOOCs that were produced at the 29 UK universities connected to the FutureLearn MOOC platform. Bringing these papers together, and considering them as a body of related work, reveals a set of nine priority areas for MOOC research and development. We suggest that these priority areas could be used to develop a strategic approach to learning at scale. We also show how the papers in this special issue align with these priority areas, forming a basis for future work.